2001
DOI: 10.1161/hc4701.099730
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Aggressive Lipid-Lowering Strategy on Progression of Atherosclerosis in the Left Main Coronary Artery From Patients in the Post Coronary Artery Bypass Graft Trial

Abstract: Background-The Post Coronary Artery Bypass Graft Trial, designed to compare the effects of two lipid-lowering regimens and low-dose anticoagulation versus placebo on progression of atherosclerosis in saphenous vein grafts of patients who had had CABG surgery, demonstrated that aggressive lowering of LDL cholesterol levels to a mean yearly cholesterol level from 93 to 97 mg/dL compared with a moderate reduction to a level of 132 to 136 mg/dL decreased the progression of atherosclerosis in saphenous vein grafts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…Past research has demonstrated the efficacy of acetylsalicylic acid and antilipid agents at reducing the risk of subsequent cardiovascular events among CAD patients with multiple comorbidities, including CABG surgery patients (8,(13)(14)(15). Thus, we expected to find fewer differences among patient subgroups.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Past research has demonstrated the efficacy of acetylsalicylic acid and antilipid agents at reducing the risk of subsequent cardiovascular events among CAD patients with multiple comorbidities, including CABG surgery patients (8,(13)(14)(15). Thus, we expected to find fewer differences among patient subgroups.…”
Section: Discussionmentioning
confidence: 89%
“…Although many patients had comorbidities, suggesting that they would benefit from specific medical therapy, these subgroups were not always more likely to receive a specific medication than other patients. For example, the use of betablockers among patients with prior MI is well known to decrease mortality (15,16). However, patients with prior MI were found to be no more likely to receive beta-blockers than other patient subgroups at discharge and at 12 months following CABG surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Similar findings were reported by the larger Post-CABG Trial that involved 1351 patients who had surgery 1 to 11 years previously. [7][8][9] Compared with patients randomized to lovastatin 5 mg/d, patients randomized to lovastatin 40 mg/d had a lower incidence of vein graft occlusive disease and less cardiovascular morbidity and mortality 4 years after randomization. [7][8][9] The 2 studies described above enrolled relatively healthy male patients under the age of 65 years who had undergone surgery several years earlier.…”
Section: Discussionmentioning
confidence: 99%
“…The Post-CABG Trial demonstrated that aggressive cholesterol treatment with lovastatin reduced the progression of vein graft disease and cardiovascular morbidity and mortality. [7][8][9] In contrast to the patients enrolled in the Post-CABG Trial, CABG patients in the current era are older, have more coexisting conditions, and are increasingly likely to be female. 10 Moreover, the Post-CABG Trial enrolled patients several years after they had undergone surgery (55% of patients had undergone surgery Ͼ5 years previously), with saphenous vein graft atherosclerosis likely already in progress.…”
Section: Clinical Perspective P 1792mentioning
confidence: 99%